2015
DOI: 10.1080/23311916.2015.1094017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon nanotubes by arc-discharge and chemical vapor deposition method with analysis of its morphology, dispersion and functionalization characteristics

Abstract: In this paper Multi-walled carbon nanotubes are synthesized by arc-discharge and chemical vapor decomposition methods. Multi-walled carbon nanotubes are synthesized on thin film of nickel sputtered on silicon substrate by thermal chemical vapor deposition of acetylene at a temperature of 750°C. The flow of current in arc-discharge method varies in the range 50-200 Amps. Further arc-synthesized carbon nanotubes are characterized by X-Ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 41 publications
(28 reference statements)
1
32
0
Order By: Relevance
“…As-synthesized SWCNTs have also been further analyzed via various methods of separation to develop enriched ensembles of metallic-and semiconducting-SWCNTs [7], to further facilitate research and a move from the lab to the retail market. Synthesis of SWCNTs has thus always been key in progressing this field of research, with various techniques having been developed for this, including arc discharge [8,9], laser ablation [10,11], and chemical vapor deposition (CVD) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As-synthesized SWCNTs have also been further analyzed via various methods of separation to develop enriched ensembles of metallic-and semiconducting-SWCNTs [7], to further facilitate research and a move from the lab to the retail market. Synthesis of SWCNTs has thus always been key in progressing this field of research, with various techniques having been developed for this, including arc discharge [8,9], laser ablation [10,11], and chemical vapor deposition (CVD) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In all samples a strong peak near 2θ = 26° are related to (002) planes of hexagonal graphite structure. In some literatures this peak has been related to the formation of multi wall CNTs [20,24,25]. As SEM results revealed, CNTs diameter in sample #2 is greater than samples #4 and #5.…”
Section: Resultsmentioning
confidence: 62%
“…XRD analysis revealed the hexagonal graphite structures with enhanced d-spacing. It can be concluded that arc discharge in liquid is a very cheap method for production of CNTs and the best concentration of sodium chloride solution in DI water is 0.3 M [25].…”
Section: Resultsmentioning
confidence: 99%
“…4.3. This method has the advantage of producing CNTs of superior quality with very high tensile strength (Sharma et al, 2015). However, in the LA technique the CNTs are produced by hitting a graphitic object with a high-speed laser beam, as shown in Fig.…”
Section: Methods Of Preparation Of Carbon Nanotubesmentioning
confidence: 99%